Assessing the Theoretical Efficacy of Combination Therapy Against Gram-Negative Infections in Neutropenic Pediatric Cancer Patients: Insights from the Statistical Analysis of Survey Data - Elio Castagnola; Francesca Bagnasco; Alessio Mesini; Philipp K. A. Agyeman; Roland A. Ammann; Marta Arrabito; Fabianne Carlesse; Maria Rosaria D’Amico; Giovanna Giagnuolo; Gabrielle M. Haeusler; Evgeny A. Idelevich; Christa Koenig; et al. (Antibiotics)
Background: Empirical antibacterial therapy for febrile neutropenia reduces mortality due to Gram-negative blood stream infections (BSIs). Pediatric guidelines recommend monotherapy with an antipseudomonal beta-lactam or a carbapenem and to add a second anti-Gram-negative agent in selected situations. We evaluated the changes in the proportions of resistance of beta-lactam monotherapies vs. their combination with amikacin, and the possible impact on ICU admission or death. Results: 797 BSIs due to Gram-negative bacteria in 685 patients were included. Combination therapies with amikacin had a lower percentage of isolates resistant to one or to both drugs compared with the respective monotherapy. The highest OR for ICU admission was observed when both drugs of the combination of meropenem–amikacin were resistant. Mortality was significantly associated with relapse or the progression of the underlying malignancy, and resistance to both drugs of the combinations of cefepime–amikacin or meropenem–amikacin. Methods: This study was based on data collected for a large multinational study, in which the susceptibility of Gram-negative bloodstream isolates was categorized following either EUCAST or CLSI according to local laboratory standards. An escalation antibiogram was generated for each selected drug. For resistant bacteria, the conditional susceptibility probability on resistance was calculated. Conclusions: In pediatric cancer patients with Gram-negative BSIs, the proportion of the resistant organism correlates with ICU admission or death, which may be reduced by combination therapy. In patients with suspected or confirmed Gram-negative BSIs that are not-improving or deteriorating under monotherapy, escalation to meropenem may represent the best option. Amikacin should be preferred when combination therapy is considered with ciprofloxacin as an alternative in the case of impaired renal function.